Letting Wood Rot: A Case Study on Local Perceptions of Global Conservation Initiatives (Boumba, Niger) - Jocelyn Müller; Iro Dan Guimbo (Ethnobiology Letters, 2011)
Although there is a pressing need for conservation in Africa and a push for such actions to be directed by the community, there is still much conflict both in academia and on the ground regarding the success and methods of community-based conservation. Employing key-informant interviews, focus group discussions and participant observation, we look at how one community has perceived the conservation actions in their village, Boumba, Niger, and the neighbouring national park, Park-W. This study examines local perceptions of the goals, priorities and methods of conservation in Park-W and the Boumba region. We demonstrate that while participants expressed positive alignment with perceived conservation goals, they did not agree with conservation priorities and felt strongly against the methods.  Reframing conservation discourse in the terms of sustainable-use or adaptive management may serve to help translate much of the conservation ethic to local realities. We argue that for local conservation to be culturally sustainable, programmers of conservation must engage the community on their own terms, and recognize the value of local perceptions.